Diosbulbin B-Induced Mitochondria-Dependent Apoptosis in L-02 Hepatocytes is Regulated by Reactive Oxygen Species-Mediated Autophagy - Ye, Jing; Xue, Mei; Liu, Yamin; Zhu, Sirui; Li, Yu; Liu, Xiaoli; Cai, Danhong; Rui, Jia; Zhang, Liang (Frontiers in Pharmacology, 2019)
Aim: Diosbulbin B (DB) is a major diterpenoid compound found in Dioscorea bulbifera L, a traditional medicinal herb in China. Clinical reports have confirmed that Dioscorea bulbifera L. can induce significant hepatotoxicity. In this study, we showed that DB can induce mitochondria-dependent apoptosis and investigated the role of autophagy in DB-induced hepatotoxicity in L-02 hepatocytes. Methods: L-02 hepatocytes were treated with different concentrations of DB for 48 h, after which indicators of autophagy and apoptosis were measured. 3-methyladenine (3-MA) and rapamycin (Rapa) were used as inhibitor and agonist of autophagy, respectively. Furthermore, the reactive oxygen species (ROS) scavenger N-acetyl-L-cysteine (NAC) was used in combination with DB to evaluate the relationship between ROS and autophagy. Results: L-02 cell viability was significantly decreased after treatment with DB for 48 h. Additionally, DB induced concentration-dependent apoptosis and autophagy and, increased the activities of caspase-3, caspase-9, alanine aminotransferase (ALT) and aspartate transaminase (AST), and induced excessive leakage of lactate dehydrogenase (LDH). Inhibition of autophagy by 3-MA increased DB-induced apoptosis, resulting in aggravation of hepatotoxicity. Conversely, treatment with Rapa increased malondialdehyde (MDA) content and reduced superoxide dismutase (SOD) activity. Moreover, we found that DB treatment increased the level of intracellular ROS, decreased the mitochondrial membrane potential (MMP) and adenosine triphosphate (ATP) production, and caused abnormal opening of the mitochondrial permeability transition pore (mPTP), which, were finally restored by the ROS scavenger NAC. Conclusions: Accumulation of ROS can induce mitochondria-dependent apoptosis and likely to play a key role in DB-induced hepatocellular injury. Activation of autophagy may inhibit apoptosis, but also reduces antioxidant capacity.